Women in Polish banking during the Second Polish Republic - Leszczyńska, Cecylia (Studia Historiae Oeconomicae, 2019)
This paper aims to analyse the employment of women in banking during the Second Polish Republic (i.e. interwar Poland). The banking sector was small in terms of employment. The number of people associated with this sector was 18.1 thousand in 1921 and 31.2 thousand in 1931, which accounted for 0.5-0.6% of all professionally active workers outside the agricultural sector. The banking community was dominated by men, the number of women working in banks was about 6.1 thousand in 1921 and 8.5 thousand in 1931 (30% of all human resources). This paper presents the nature of jobs performed by women, their positions and earnings. The presentation takes a number of forms: according to bank types, groups of voivodeships, size of the town and according to headquarters and branches. In all cases, the activities and earnings of women and men were compared.